2016
DOI: 10.1039/c6ja00280c
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution continuum source graphite furnace atomic absorption spectrometry for the monitoring of Au nanoparticles

Abstract: This article demonstrates the potential of HR CS GFAAS for establishing the presence of NPs and their average size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Se puede observar que al representar los diferentes tamaños aparecen dos regiones lineales; una primera de mayor sensibilidad desde los iones de oro hasta las nanopartículas de 20 nanómetros y la segunda de menor sensibilidad desde 20 nm hasta la muestra de 100 nm. [3] Sin embargo, esta correlación presenta el problema de que las señales de Au (III) no son unimodales y gaussianas como las nanopartículas, si no que presentan una cola adicional, que se superpone a la región de aparición de NPs. Esto podría deberse a que durante la aplicación del programa de temperaturas se estén formando NPs en proporciones y tamaños variables.…”
Section: Experimental Y Resultadosunclassified
“…Se puede observar que al representar los diferentes tamaños aparecen dos regiones lineales; una primera de mayor sensibilidad desde los iones de oro hasta las nanopartículas de 20 nanómetros y la segunda de menor sensibilidad desde 20 nm hasta la muestra de 100 nm. [3] Sin embargo, esta correlación presenta el problema de que las señales de Au (III) no son unimodales y gaussianas como las nanopartículas, si no que presentan una cola adicional, que se superpone a la región de aparición de NPs. Esto podría deberse a que durante la aplicación del programa de temperaturas se estén formando NPs en proporciones y tamaños variables.…”
Section: Experimental Y Resultadosunclassified
“…Lipstick is found in different forms as solid (stick), semi-solid (jars), and liquid (tube). The different types of lipsticks are Sheer and Satin, Moisturizing, Matte, Glossy, Frosted, and Cream (Mailgyurai et al, 2015;Resano et al, 2016). A woman is suspected to ingest 1.8 kg of lipstick in her lifetime (Soares and Nascentes, 2013).…”
Section: Research Articlementioning
confidence: 99%
“…The work by Resano et al 72 showed that HR CS GFAAS could be applied to other NPs beside Ag, which was the focus of the previous works. Also, the use of different parameters to quantify the presence and the size of NPs was discussed, and it was concluded that the time of appearance of the peak maximum was the preferred one in this case, as it did not depend on the concentration and permitted to appreciate clear differences according to the particle size, as shown in Figure 5.…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%
“…Still, more work is needed in order i) to develop a more unified methodology and even terminology; ii) to further improve the selectivity of the technique, as right now it is difficult to resolve mixtures of NPs or of NPs with ionic species, requiring the use of deconvolution approaches 72,73 or of previous separations (in this regard, cloud point extraction has been reported to enable the selective quantification of AgNPs and of total Ag in waters with a LOD of 2 ng L -1 using HR CS GFAAS 76 ); and, iii) to demonstrate the applicability of this approach to other types of NPs.…”
Section: Further Work Has Basically Confirmed the Potential Of The Tementioning
confidence: 99%